Representasi Maskulinitas Perempuan dalam Iklan Sasa Melezatkan berjudul Perempuan Serba Bisa - Ramadhani, Fadila Elma; Budiyono, Alief (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2024)
Advertising has a big influence in shaping people's perceptions and views on various issues, including gender and the role of women. This research analyzes the representation of women's masculinity in the Sasa Melezakan advertisement entitled "Versatile Women" using Charles Sanders Peirce's semiotic approach. By analyzing visual signs such as the appearance, movements and activities of women shown in advertisements, this research reveals that these advertisements strongly represent women's masculinity in various fields that challenge traditional gender stereotypes. Semiotic analysis reveals that this advertisement features women in roles such as professional athletes, business leaders, and skilled racers, redefining the concept of femininity and breaking down the boundaries of gender roles that have been considered rigid. The representation of female masculinity in this advertisement is a statement to expand the definition of femininity and challenge gender norms that limit women. This research contributes to studies on gender, media and representation by analyzing how the advertising industry responds to and reflects social changes regarding the role and potential of women in society.